TWO FELLING TECHNIQUES AND FELLER POSTURES FOR INCREASING THE UTILIZATION OF GMELINA WOOD (A case study at two timber estates in East Kalimantan) - Suhartana, Sona; Yuniawati, Yuniawati (Secretariat of Forestry Research and Development Agency, 2006)
Fellingis an early step in timber utilization process. Efficiencyand effectivity of felling technique, tool type and feller posture will affect the whole timber utilization efficiency. This study was carried out at two timber estates in East Kalimantan and intended to see the effect of two felling techniques and feller postures on felling productivity, fellingcost, as well as timber utilization efficiency.Primary data collected in this research included : felling time, volume of felled timber, productivity, felling efficiency, stump height and felling cost. The data was analyzed using split-plot design with factorial pattern.The result showed that the implementation of lowest possible felling technique (LPFI) increased log production from 14.4 to 17.7%. The lowest stump height left was of the one using LPFf with particular bowed posture in PT. Sumalindo Lestari Jaya I (SLJ I) (4.82 cm).